A critical study of the educational problems of the non-Christian tribes of the Mountain Province - Tadaoan, Pio M. 1917- (1953)
The weaknesses of the school system as well as some of the educational policies enforced among the Non-Christian tribes of the Mountain Province were determined in this study. The weaknesses and their probable causes, alleged by the investigator to be existing, are delineated in this study. These causes have been inferred from the evidence gathered in the course of the investigation. This work will also take account of the remedial measures undertaken for the improvement of education among tribes.
Typewritten.
Vita.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Education -- Philippines -- Mountain Province